Miscibility And Reinforcing Ability Of Allylic Monomers In Polystyrene - Muhammad, Ahmad Fakhrughazi (Universiti Sains Malaysia, 2017)
The use of diallyl-ortho phthalate (DAOP) as reactive plasticiser of Polystyrene/diallyl-ortho phthalate blends (PS/DAOP) was studied. The solubility parameters, glass transition temperature (Tg) and morphology of the 100wt% PS and reactive plasticized 80PS/20DAOP blends over a wide range of compositions were investigated. Dicumyl peroxide (DCP) was used to initiate the cure reaction of DAOP. Curing of DAOP with 3phr of DCP using DSC indicated single exothermic peak. Tg’s of the 80PS/20DAOP, 80PS/20DAOP-DCP uncured and various 80PS/20DAOP-DCP cured blends were obtaining through the DSC scan and the result was compared with Fox equation. The solubility parameter calculation according to Hildebrand has been used to determine the miscibility of PS and DAOP by using Fedor’s, Small and Van Krevelan method. In order to dissolved PS, the solubility parameter of solvent such as toluene and tetrahydrofuran (THF) also have been calculated. In thermoplastic-plasticizer system, Tg reduced with increasing amount of plasticizer suggesting that processibility improve with the expense of reduction of thermomechanical properties. While, in thermoplastic-reactive plasticizer, successful application of reactive plasticizer in thermoplastic normally shown by the ability to retain the thermomechanical properties (Tg) of the thermoplastic on DSC curing of DAOP with DCP initiator. In other hand, the final morphology and thus properties of blends affected by a few factors such as compositions and cure temperature. Evidence of phase separation and changes in the morphology that is important to determine the Tg and examine morphology of cured blends.